Property evolutions of Si/mixed Yb2Si2O7 and Yb2SiO5 environmental barrier coatings completely wrapping up SiCf/SiC composites under 1300 °C water vapor corrosion. Issue 16 (15th August 2021) - Jian, Yingjie; Wang, Yanfei; Liu, Rongjun; Wan, Fan; Zhang, Jin
Abstract: A bi-layer environmental barrier coating (EBC) consisting of silicon(Si) bond coat/mixed ytterbium disilicate (Yb2 Si2 O7 ) and ytterbium monosilicate (Yb2 SiO5 ) topcoats has been successfully prepared to completely wrap up the SiCf /SiC composites and the protective effects of such EBC have been evaluated by soaking them in a mixed 50% O2 and 50% H2 O corrosive gases at 1300 °C for various times. In topcoats, Yb2 Si2 O7 is the major phase, providing good thermal expansion coefficient (CTE) matching with composite substrate and thus excellent thermal shock resistance, whereas Yb2 SiO5 is the dispersing minor phase, providing improved water vapor corrosion resistance. The completely wrapping up of SiCf /SiC composites by above EBC system is employed to avoid direct exposure to the corrosive conditions, making it possible to evaluate the genuine protection effects of current EBCs. Under 1300 °C water vapor corrosion, the mass change, the phase composition and the evolution of microstructure are investigated, which suggest that the bi-layer EBC has excellent performance on protecting SiCf /SiC composites from water vapor corrosion at 1300 °C.